Evaluasi Formulasi Sediaan Mikroenkapsulasi Ekstrak Etanol Herba Seledri (Apium graveolens L.) - Najwa Aisyah; Razoki Razoki; Hariyadi Dharmawan Syahputra (Lembaga Pengembangan Kinerja Dosen, 2026)
Celery (Apium graveolens L.) is an herbal plant containing bioactive compounds such as flavonoids, alkaloids, tannins, saponins, and triterpenoids that have the potential to lower blood glucose levels. However, the stability and absorption of its active compounds still need to be developed. One effort to improve the stability and effectiveness of the extract is through microencapsulation technology. This study aims to formulate and evaluate the physical characteristics of microencapsulated preparations containing celery herb ethanol extract. The method used includes making the extract by maceration technique using 80% ethanol, then formulation using alginate and chitosan polymers with ionic gelation method using CaCl2 solution. Evaluation of the preparation includes stability test, water content and adhesion test on the gastric mucosa. The results showed that the microcapsules remained stable, there were no physical changes after six cycles. The adhesion test showed that the extract concentration of 0% (blank) had the highest adhesion ability and the lowest water content was 0.25%.